Desenvolvimento de perfis extrudados de compósitos de polietileno de alta densidade com farinha de madeira - Santi, Cristiano Ribeiro de (2009)
Polymer profiles extrusion shows some peculiarity due to the flow behavior of these materials during the processing. On the other hand, the profile die design and tooling has been more a result of professional s expertise than an engineering project in essence. In the present work, it was aimed to combining concepts of computer s aided engineering to rheological behavior of wood thermoplastic composites on profile die design. The prepared formulation where comprised of 60%wt HDPE, with and without a coupling agent, compounded with up to 40%wt wood flour and lubricant. Rheological properties in capillary and oscillatory rheometry were investigated. Due to experimental difficulties found in such rheometry methods when large particle size fillers are present or in highly loaded systems, a systematic approach for data collecting from a torque rheometer was evaluated, together with a mathematical model for power law parameters evaluation, where the results has been found in agreement to the data of capillary and oscillatory rheometry for neat polymers. For the composites, the results of torque and capillary rheometry virtually coincide, but the viscosities are lower than those measured in oscillatory rheometry. Simulation software was employed both in the die design and experimental data explanation. A cooled land die attached to a single screw extruder was employed for profile extrusion. Once steady extrusion conditions were achieved, temperature, pressure and linear output were monitored and profile s samples were cut for mechanical properties evaluation in flexural mode. The results shown that linear output and profile s properties were influenced by a combination of factors associated to composite formulation, processing conditions and die cooling. The optimum processing conditions for uniform profile extrusion could be reproduced by computer simulation.